2011
DOI: 10.1002/sia.3878
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the damage on the outermost hair surface using ToF‐SIMS and XPS

Abstract: The outermost surface of the human hair is covered with a thin layer of fatty acids bonding proteins, which plays an important role in giving hair a soft and smooth feeling and surface hydrophobicity. In this study, changes in fatty acids and protein fragment ions were characterized using time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) to investigate hair damage. As a result, the intensity of the fragment ion m/z 76 related to cystine and cysteine, major com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…Consequently, it was confirmed that the surface cuticles of the subjects elder than 40 are prone to be broken and this phenomenon is promoted by aging . It has been variously reported that reduction of 18‐MEA badly affects hair and that chemical treatments, such as bleaching, cause its drastic loss . In this study, it was revealed that aging also causes loss of 18‐MEA, especially in the age range elder than 40.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Consequently, it was confirmed that the surface cuticles of the subjects elder than 40 are prone to be broken and this phenomenon is promoted by aging . It has been variously reported that reduction of 18‐MEA badly affects hair and that chemical treatments, such as bleaching, cause its drastic loss . In this study, it was revealed that aging also causes loss of 18‐MEA, especially in the age range elder than 40.…”
Section: Discussionmentioning
confidence: 67%
“…It has been variously reported that reduction of 18-MEA badly affects hair and that chemical treatments, such as bleaching, cause its drastic loss. 6,[11][12][13][14][15] In this study, it was revealed that aging also causes loss of 18-MEA, especially in the age range elder than 40. A number of significant changes in hair properties (diameter, density, luster, bending elasticity, lipids, minerals, etc.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Figure 3 shows the TEM observation of cuticle cells and the depth profiling data of Cys/Cyc in the first cuticle layer. In the detection of the Cys/Cyc peak (m/z 76), it was confirmed that the overlapping of other peaks, such as C 6 H 4 , was small; thus the variation of peak intensity mainly reflected the change in Cys/Cyc composition [22]. It is indicated that a single layer of cuticle consists of sev- eral tissue layers, as a consequence of the peak intensity changes resulting from the difference in the Cys/Cyc composition of each tissue.…”
Section: Fig 2 Comparison Of the Tem Image Of The Hair Surface Crosmentioning
confidence: 82%
“…This is consistent with the stripping of the β-layer which commonly occurs in damaged hair. 20,21,[42][43][44] The partial splaying that occurs at the edge of the cuticle cell 45 , as well as external damage, as mentioned above with regard to the lipid β-layer, provided the opportunity to investigate the layering of the edge of the cuticle cell. Spectra across the edge, covering individual layers, showed significant changes to the amide, lipid and cystine-related regions.…”
Section: Discussionmentioning
confidence: 99%